Penyuluhan interaktif tentang kesiapan mental ibu muda dalam mengelola tumbuh kembang anak - Dewi, Indah Maulina; Rum, Malihah Ramadhani; Indriyani, Hajir; Silahoy, Ice Meriah Hertanti; Daeli, Joverius; Erawati, Nieke; Krisna, Krisna; Auliah, Devi; Anisah, Dhea Muthia; Maura, Melisa Safa (JOURNAL of Public Health Concerns, 2025)
Background: The mental health of young mothers is a crucial aspect influencing family well-being and child development. However, mental health literacy among this group is still limited, necessitating educational efforts through appropriate counseling methods. Health promotion is the process of "enabling communities to increase control and improvement of their health," encompassing physical, mental, and social aspects. Health education, as a promotional strategy, aims to influence individual and group behavior to support improved health. Purpose: To increase young mothers' knowledge about mental health in managing and addressing children's growth and development. Method: The activity was conducted on August 25, 2025, at the Yuliarpan Medika 2 Clinic, Cibitung District, Bekasi Regency. The activity involved 30 respondents, young mothers with children under two years old and in need of education regarding mental preparedness in addressing their children's behavior. The implementation of this mental health education activity for young mothers used an interactive, participatory approach combining lectures, group discussions, and question-and-answer sessions. The instruments used were an educational leaflet and a 10-question questionnaire covering aspects of mental attitudes in addressing children's behavior and development. Results: Data revealed that the majority of respondents were young mothers of productive age, aged 26-30 (18 respondents, 60.0%), with an average age of 29.5 years, with a standard deviation of ±2.4. Educational levels varied considerably, but the majority were junior high school graduates (12 respondents, 40.0%) and high school graduates (10 respondents, 33.3%). The majority of respondents worked as housewives or employees (9 respondents, 30.0%). There was an increase in respondents' knowledge, from an average pre-test score of 72.7 points to 89 points in the post-test. Conclusion: The interactive counseling in this activity was highly effective in increasing understanding of young mothers' mental readiness and self-management in dealing with children's growth and development. This increased knowledge also had a positive impact on young mothers' ability to manage time, emotions, and stress in family life. Suggestion: Mental health counseling for young mothers should be conducted regularly, with additional material on the biological impacts of stress and coping strategies that can be applied in everyday life. Keywords: Child development; Early marriage; Health education; Mental readiness Pendahuluan: Kesehatan mental ibu muda merupakan aspek penting yang berpengaruh terhadap kesejahteraan keluarga dan tumbuh kembang anak. Namun, tingkat literasi kesehatan mental pada kelompok ini masih terbatas sehingga diperlukan upaya edukasi melalui metode penyuluhan yang tepat. Promosi kesehatan adalah proses untuk “memungkinkan masyarakat meningkatkan pengendalian dan perbaikan kesehatan mereka,” yang mencakup aspek fisik, mental, dan sosial. Penyuluhan kesehatan, sebagai salah satu strategi promosi, bertujuan memengaruhi perilaku individu dan kelompok agar mendukung peningkatan derajat kesehatan. Tujuan: Untuk meningkatkan pengetahuan ibu muda mengenai kesehatan mental dalam mengelola dan menghadapi perilaku tumbuh kembang anak.   Metode: Kegiatan dilaksanakan pada tanggal 25 Agustus 2025 di Klinik Yuliarpan Medika 2, Kecamatan Cibitung, Kabupaten Bekasi. Kegiatan melibatkan 30 responden yang merupakan ibu muda yang memiliki anak di bawah dua tahun dan membutuhkan edukasi terkait kesiapan mental dalam menghadapi perilaku anak. Pelaksanaan kegiatan penyuluhan kesehatan mental bagi ibu muda ini menggunakan pendekatan interaktif partisipatif yang menggabungkan metode ceramah, diskusi kelompok, dan sesi tanya jawab. Instrumen yang digunakan berupa edukatif leaflet dan kuesioner dengan 10 pertanyaan meliputi aspek sikap mental dalam menghadapi perilaku dan tumbuh kembang anak. Hasil: Mendapatkan data bahwa sebagian besar responden adalah ibu muda berusia produktif yaitu di rentang usia 26 - 30 tahun yaitu sebanyak 18 (60.0%), rata-rata berusia 29.5 tahun dengan simpangan baku ±2.4. Tingkat pendidikan cukup bervariasi, namun mayoritas adalah lulusan SMP sebanyak 12 (40.0%) dan SMA sebanyak 10 (33.3%). Sebagian besar responden bekerja sebagai ibu rumah tangga atau karyawan yaitu masing-masing 9 orang (30.0%).Terdapat peningkatan pengetahuan responden dari rata-rata nilai pre-test peserta sebesar 72.7 poin menjadi 89 poin pada post-test. Simpulan: Penyuluhan interaktif dalam kegiatan ini, sangat efektif dalam meningkatkan pemahaman mengenai kesiapan mental ibu muda dan pengelolaan diri dalam menghadapi perilaku tumbuh kembang anak. Peningkatan pengetahuan juga memberikan dampak positif pada ibu muda dalam mengelola waktu, emosi dan stress dalam menjalani hidup berkeluarga. Saran: Penyuluhan kesehatan mental bagi ibu muda perlu dilakukan secara rutin dengan penambahan materi mengenai dampak biologis stres dan strategi coping yang dapat diterapkan dalam kehidupan sehari-hari.